MAKNA SALĀM DALAM AL-QUR’AN (Analisis Semiotika Charles Sanders Peirce) - Nurun Nisaa Baihaqi (Taqaddumi: Journal of Quran and Hadith Studies, 2021)
Salām has been understood by the wider community as merely an expression or greeting sentence, namely assalāmu‘alaikum and wa‘alaikumussalām. Whereas in the al-Qur'an, salām can be interpreted broadly. This study aims to find the signs of the word salam found in several verses of the Qur'an by using a semiotic approach. In this case, the writer uses Charles Sanders Peirce's theory of semiotics, namely trichotomy (representamen, object and interpretant) to reveal the meaning of greetings in the Qur’an as a sign. The method of this research is qualitative content analysis, namely research that aims to identify the message of a media as the object of research. From the results of the study it can be concluded that the greeting is not only interpreted as a sentence or greeting, but also means al-salām (the name of Allah), al-khair (kindness in speech and action), al-tsanā al-hasan (good praise to the The Prophet), al-Salāmah min al-Syarri (survived ugliness) and the eschatological aspect, namely respect for the experts of heaven and darussalam (heaven). Research like this needs to be developed in order to expand the study of the Qur'an and prove the flexibility of the Qur'an in various spaces and times.